2010
DOI: 10.4103/0973-1075.73643
|View full text |Cite
|
Sign up to set email alerts
|

Caring for dying people: Attitudes among Iranian and Swedish nursing students

Abstract: Aim:To compare the attitudes of Iranian and Swedish nursing students toward caring for dying persons.Materials and Methods:Their attitudes were measured with the Frommelt’s Attitude Toward Caring of the Dying and the Death Attitude Profile Revised.Results:The results indicated that the participating Iranian students were more afraid of death and less likely to give care to dying persons than the Swedish participants.Conclusion:It is suggested that theoretical education should be individualized and culturally s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 26 publications
7
41
0
Order By: Relevance
“…In other words, students who were older and had a more natural perception of death had a less negative attitude towards caring for people who were dying compared with those who were younger and had a less natural perception of death. Other components that influence attitudes toward caring for dying patients, from the students' point of view, are fear of death and religiosity, which are factors that are reported to increase negative feelings (Iranmanesh et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, students who were older and had a more natural perception of death had a less negative attitude towards caring for people who were dying compared with those who were younger and had a less natural perception of death. Other components that influence attitudes toward caring for dying patients, from the students' point of view, are fear of death and religiosity, which are factors that are reported to increase negative feelings (Iranmanesh et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of other factors come in to play such as culture and religion and psychosocial aspects of care. Iranmanesh et al [23] in their comparison of Iranian and Swedish nursing students, found that attitudes towards palliative care differed substantially across cultures and suggested of palliative care.…”
Section: The Death Experience For Different Patient Populationsmentioning
confidence: 99%
“…Garity feels this is necessary to avoid moral distress and retain nurses in practice and is also supported by external agencies which frequently accredit nursing courses. The need to address cultural sensitivity [23] and ethnic background [19] was also raised as an issue in relation to education strategies.…”
Section: The Death Experience For Different Patient Populationsmentioning
confidence: 99%
“…The Death Attitude Profile-Revised (DAP-R) was also added and utilized in one of the studies (Iranmanesh et al, 2008). Other studies added information about the correlation between the characteristics of nursing students and FATCOD-B Score in the aims of study (Arslan et al, 2014;Iranmanesh, Axelsson, Häggström, & Sävenstedt, 2010). However, there is no evidence of studies which explore attitudes toward caring in dying patients in Indonesia.…”
mentioning
confidence: 99%